The mediating role of flow experiences in the relationship between academic procrastination and academic life satisfaction among undergraduate students - Gülçin Güler Öztekin; Amelia Rizzo; Abdulmohsen Mohammed Abdullah Alkhulayfi; Murat Yıldırım (Discover Psychology, 2025)
Abstract Academic life satisfaction is an important indicator of students' contentment with both their academic and personal environments. Therefore, determining the factors that promote academic life satisfaction is of great importance. This study aimed to investigate the mediating role of flow experiences in the association between academic procrastination and personal satisfaction and satisfaction with the academic environment. A total of 581 undergraduate students (65.4% women) participated in the study. The students' ages ranged from 18 to 25 years, with an average age of 20.44 years (SD = 2.02). This study found that academic procrastination was negatively associated with flow experiences, personal satisfaction and satisfaction with the academic environment. Flow experiences were positively associated with personal satisfaction and satisfaction with the academic environment. Flow experiences acted as a mediator in the association between academic procrastination and personal satisfaction and satisfaction with the academic environment. The study findings show that academic procrastinators may have difficulty in experiencing flow, which in turn leads to poor academic life satisfaction. This study addresses the need for practices aimed at reducing academic procrastination and experiencing flow in interventions to enhance academic life satisfaction among university students.